Particularidades do teorema de Poncelet - Almeida, Marcos Antonio Felix de (2014)
In this work we study some applications of the Poncelet's Theorem for teaching geometry. One of our main motivations for this work is that in some the high school leved math courses the study of geometry is slightly used and in certain circunstances the theorems are not demonstrated to the knowledge of the theories discussed. Finally, a list of exercises is proposed.